LGG-31. Pediatric low-grade gliomas with FGFR1 mutations and spontaneous hemorrhage: case series. (3rd June 2022) - Campion, Stephani; Aguilar-Bonilla, Ana E; Elbabaa, Samer; Smith, Amy A
Abstract: Pediatric low-grade gliomas (pLGG) are the most common pediatric CNS neoplasms. Thanks to the advent of molecular tumor diagnostics, we have begun exploring the clinical relevance of FGFR1 (c.1632C>A; p.N546K) mutations in the pLGG population. However, the risk of spontaneous hemorrhage in pLGG patients harboring FGFR1 mutations is even less understood. We present four pLGG cases with FGFR1 mutation and hemorrhagic episodes. Patient 1 presented with an intraventricular hemorrhage and leptomeningeal disease. Pathology was consistent with suprasellar pilocytic astrocytoma, FGFR1, and PTPN11 mutations. Initial therapy consisted of Carboplatin/Vinblastine per ADVL0515. The patient has had several recurrences, and treatment regimens have included ACNS0223, Everolimus, and A9952 regimen A. Patient 2 was diagnosed with an optic pathway glioma, and pathology confirmed FGFR1, MEK2, PTPN11, and NF1 splice site mutations. The patient also has a history of Noonan's Syndrome and has undergone several chemotherapy regimens, including A9952 Regimen A, COG MATCH with Erdafitinib, and Avastin. The best tumor response was seen while on Avastin. The patient has presented with two episodes of intratumoral hemorrhage, both after treatment with Avastin. Patient 3 presented with a sudden brain stem hemorrhage and underwent a biopsy and debulking. The pathology was consistent with a pilocytic astrocytoma with an FGFR1 mutation confirmed by Next-generation sequencing (NGS). Treatment regimens for this patient include A9952 Regimen A and Vinblastine. Patient 4 presented with acute headache and vomiting and was found to have a hemorrhagic suprasellar mass. The patient underwent tumor debulking, and pathology was consistent with low-grade glioma. NGS revealed FGFR1 and KRAS mutations. The patient received therapy as per A9952 Regimen A. Greater surveillance of this molecular and clinical finding is warranted to uncover the association between FGFR1 mutations and hemorrhage in patients with low-grade gliomas.